Herpetic esophagitis and eosinophilic esophagitis: A potential association - Quera, Rodrigo; Sassaki, Ligia Yukie [UNESP]; Núñez, Paulina; Contreras, Luis; Bay, Constanza; Flores, Lilian (International Scientific Information, 2021)
Background: Gastroesophageal reflux disease, infectious esophagitis, and eosinophilic esophagitis are the most frequent causes of esophagitis, the latter 2 etiologies being generally considered independently. However, the associa-tion between both entities has been suggested through case reports in immunocompetent patients. We present the case of an immunocompetent 26-year-old man presenting with fever, adynamia, retrosternal pain, and dysphagia. Endoscopy was performed, showing whitish lesions in circular plates with erosions, and in some depressed areas in the middle and distal esophagus. Biopsies showed the presence of ulcerated foci covered by fibrinoleukocyte exudate in granulation tissue and nuclear inclusions with a viral appearance. The immunohistochemical study for herpes simplex virus (HSV) was positive. The patient was treated symptomat-ically and progressed favorably. The endoscopic control carried out at 3 months showed longitudinal grooves and trachealization, findings compatible with the diagnosis of eosinophilic esophagitis and with biopsies that confirmed the etiology by showing an increase in eosinophil count >20 per field, without isolating HSV. This clinical case confirms the possible relationship between esophagitis caused by HSV and eosinophilic esoph-agitis. Alterations at the immune level and damage to the esophageal mucosa barrier may explain this relation-ship. In this scenario, an endoscopic follow-up should be considered.
Keywords: Eosinophilic Esophagitis; Esophagitis; Immunocompetence; Keratitis, Herpetic